Study on Impact of Self Efficacy on Leadership Effectiveness in IT Companies - Miska Singh (International Journal of Science and Society, 2021)
Leadership is a crucial desire for all kinds of organizations. If the answer to the question, “what is meant leadership to the people in corporate?” is explored the answer will be in variety and will give various perspectives of leadership. This is because leadership is something unique in every different unique situation. There are leaders in various organizations but all of them lead in their own different ways and styles and many times they are successful too. The reason for having different answers on leadership is that every superior lead in different way and every subordinate experiences different style and pattern of leadership and in many times also witnesses the success of the organization. Some define leader as who influences other and encourages them to work, others feel good leader is one who guides others, and some think leader is the one who empowers his/her subordinates. Leadership has continuously evolved because of situational changes like changes in external environment and/ or changes in internal settings of organization.